Thermal and hygric physiology of Australian burrowing mygalomorph spiders (Aganippe spp.) - Mason, L.; Tomlinson, Sean; Withers, Philip; Main, B. (Springer, 2013)
This study investigated the standard metabolic rate (SMR) and evaporative water loss (EWL) responses of three Australian trapdoor-constructing mygalomorph spider species, two undescribed arid-zone species (Aganippe 'Tropicana A' and A. 'Tropicana B') and a mesic-dwelling species (A. rhaphiduca) to acute environmental regimes of temperature and relative humidity. There were significant effects of species, temperature, and relative humidity on SMR. SMR was lower for A. raphiduca than both A. 'Tropicana' spp. with no difference between the two A. 'Tropicana' spp. Metabolic rate increased at higher temperature and relative humidity for all three species. There were significant effects of species, temperature, and relative humidity on EWL. The mesic Aganippe species had a significantly higher EWL than either arid Tropicana species. EWL was significantly higher at lower relative humidity. Our results suggest an environmental effect on EWL but not SMR, and that mygalomorphs are so vulnerable to desiccation that the burrow provides a crucial refuge to ameliorate the effects of low environmental humidity. We conclude that mygalomorphs are highly susceptible to disturbance, and are of high conservation value as many are short-range endemics. © 2012 Springer-Verlag.